How to finance Europe's military buildup? Lessons from history - Johannes Marzian; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2025)
Europe must rapidly increase its military spending, but how? We collect 150 years of data to study what governments in similar situations have done. How were past military buildups financed? What was the relative importance of debt financing, budget cuts, and taxes? Our main finding is that budget cuts, e.g. on social or foreign affairs, were rarely used to finance military buildups. Instead, governments typically relied on a mix of deficit financing and higher tax revenues. The larger the buildup, the more dominant debt financing has been. In line with history and theory, Germany and Europe should again rely on debt financing to quickly increase its defense spending and military capabilities. To deal with the added debt burden in the medium run, governments could increase taxes, reduce subsidies and tax avoidance, and freeze the growth of social spending. Fiscal rules must not stand in the way of the defence of Europe. A warning example is the case of the UK in the 1930s, which refrained from significantly ramping up military expenditure and instead pursued a policy of balanced budgets and appeasement. Consequently, the UK was ill-prepared when Nazi Germany launched its attack. Germany should not repeat the errors made by Britain in the 1930s and should invest heavily in defense so as to deter Russia. To achieve this, defense spending should be excluded from fiscal rules both in Germany and Europe. A less clear-cut alternative would be the creation of new debt funds, such as a European financing mechanism or another "Sondervermögen" in Germany. – – Europa muss seine Militärausgaben deutlich erhöhen, aber wie? Diese Frage beantworten wir mit einem Blick in die Geschichte. Wie haben Regierungen in der Vergangenheit in ähnlichen Situationen reagiert? Wie wurden Aufrüstung und Kriege typischerweise finanziert - durch Schulden, Steuern oder Haushaltskürzungen? Hierzu sammeln und analysieren wir neue detaillierte Daten zu Staatsausgaben in 22 Ländern über einen Zeitraum von 150 Jahren. Unsere wichtigste Erkenntnis ist, dass Haushaltskürzungen, z.B. in Auswärtigen Angelegenheiten oder im sozialen Bereich, keine große Rolle spielten. Fast alle Aufrüstungen wurden kurzfristig über Defizite und höhere Steuereinnahmen finanziert. Je größer die Aufrüstung, desto stärker die Schuldenfinanzierung. Im Einklang mit ökonomischer Theorie sollten Deutschland und Europa die erhöhten Verteidigungsausgaben kurzfristig über Schulden finanzieren. Um die zusätzliche Schuldenlast zu bewältigen, könnten mittelfristig die Steuern erhöht, Subventionen und Steuervermeidung reduziert, und das Wachstum der Sozialausgaben begrenzt werden. Fiskalregeln dürfen der Verteidigung Europas nicht entgegenstehen. Ein warnendes Beispiel ist Großbritannien in den 1930ern, das auf Appeasement und eine "schwarze Null" setzte, statt die Militärausgaben zu erhöhen. Dies führte dazu, dass Großbritannien unzureichend vorbereitet war, als Nazi-Deutschland angriff. Wir sollten den schwerwiegenden Fehler Großbritanniens der 1930er vermeiden und heute ausreichend in Verteidigung investieren, um Russland abzuschrecken. Verteidigungsausgaben sollten daher von den Fiskalregeln ausgenommen werden, sowohl in Deutschland als auch in Europa. Eine weniger klare Alternative wären neue Schuldenfonds, etwa ein europäischer Finanzierungsmechanismus oder ein weiteres deutsches Sondervermögen.
Keywords: 330; Military expenditures; Fiscal multipliers; Innovation; Growth; Short- and long-run consequences of rearmament; USA; Europe; Militärausgaben; Steuermultiplikatoren; Innovation; Wachstum; kurz- und langfristige Folgen der Aufrüstung; USA; Europa